2015
DOI: 10.1111/agec.12180
|View full text |Cite
|
Sign up to set email alerts
|

Tailored to the extremes: Quantile regression for index‐based insurance contract design

Abstract: A new approach for weather index-based insurance design based on Quantile Regression (QR) to condition the yield-index dependency is developed and compared to standard regression technique. Three conceptual different risk measures, i.e., Expected Utility, Expected Shortfall and a Spectral Risk Measure, are used to evaluate the risk reducing properties of these contracts. Our findings show that QR is much more powerful in establishing the yield-index dependency and lead for all risk measures to a higher risk re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 67 publications
2
71
0
Order By: Relevance
“…This flexible index definition was found to be superior to a fixed index definition (Conradt et al 2015b). However, the definition of vegetation phases based on GDD faces several challenges, for example, that assumptions must be made on the occurrence of vegetation periods based on GDD across various crops and varieties used, and that precise knowledge of sowing dates might be required (Conradt et al 2015b). …”
Section: Literature Reviewmentioning
confidence: 91%
See 4 more Smart Citations
“…This flexible index definition was found to be superior to a fixed index definition (Conradt et al 2015b). However, the definition of vegetation phases based on GDD faces several challenges, for example, that assumptions must be made on the occurrence of vegetation periods based on GDD across various crops and varieties used, and that precise knowledge of sowing dates might be required (Conradt et al 2015b). …”
Section: Literature Reviewmentioning
confidence: 91%
“…Only a few studies have incorporated growing seasons explicitly (e.g., Kapphan et al 2012;Leblois et al 2014b;Conradt et al 2015b;Kumar et al 2016). While Kapphan et al (2012) extracted information on vegetation phases from a crop model, Leblois et al (2014a) and Conradt et al (2015b) used growing degree days to specify vegetation periods. Kumar et al (2016) identified heat-sensitive growth stages from experimental data based on observed phenological phases.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations